FAKTOR-FAKTOR YANG MEMPENGARUHI REVALUASI ASET TETAP - Reva Meiliana; Mas Ayu Febriyanti (Universitas Bandar Lampung (UBL), 2019)
This study was aimed at examining the influence of factors to fixed assets revaluation in companies listed in Indonesia Stock Exchange. Factors tested in this study is leverage, operating cash flow, firm size, stucture of assets, growth companies, IOS, ownership control, mergers, acquisitions and fixed assets revaluation. The sample in this study was determined by using purposive sampling method in order to obtain 84 sample companies with 168 observations. The data analysis used logistic regression analysis. The result of this study indicated that the variable leverage, operating cash flow, firm size, stucture of assets, growth companies, ownership control did not have effect to fixed assets revaluation, while variable mergers and acquisitions affected fixed assets revaluation.